2019
DOI: 10.1111/jvp.12756
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics of intravenous and transdermal flunixin meglumine in meat goats

Abstract: The aim of this study was to determine the pharmacokinetics and prostaglandin E2 (PGE2) synthesis inhibiting effects of intravenous (IV) and transdermal (TD) flunixin meglumine in eight adult female Boer goats. A dose of 2.2 mg/kg was administered intravenously (IV) and 3.3 mg/kg administered TD using a cross‐over design. Plasma flunixin concentrations were measured by LC‐MS/MS. Prostaglandin E2 concentrations were determined using a commercially available ELISA. Pharmacokinetic (PK) analysis was performed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 12 publications
5
29
3
Order By: Relevance
“…Recent studies have demonstrated differences in pharmacokinetics of TD flunixin meglumine between cattle and goats (Kleinhenz et al, ; Reppert et al, ). The pharmacokinetic parameters of TD flunixin in alpacas varied from goats and cattle.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies have demonstrated differences in pharmacokinetics of TD flunixin meglumine between cattle and goats (Kleinhenz et al, ; Reppert et al, ). The pharmacokinetic parameters of TD flunixin in alpacas varied from goats and cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandin E 2 inhibition has been used as a measure to determine efficacy of flunixin meglumine in several species (Kleinhenz et al, ; Königsson, Törneke, Engeland, Odensvik, & Kindahl, ; Reppert et al, ). In this study, PGE 2 inhibition was quantified for both IV and TD flunixin meglumine formulations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations